2009
DOI: 10.1203/pdr.0b013e3181961e80
|View full text |Cite
|
Sign up to set email alerts
|

Murine Model for Cystic Fibrosis Bone Disease Demonstrates Osteopenia and Sex-Related Differences in Bone Formation

Abstract: As the incidence of cystic fibrosis (CF) bone disease is increasing, we analyzed cystic fibrosis transmembrane conductance regulator (CFTR) deficient mice (CF mice) to gain pathogenic insights. In these studies comparing adult (14 wk) CF and C57BL/6J mice, both bone length and total area were decreased in CF mice. Metaphyseal trabecular & cortical density were also decreased, as well as diaphyseal cortical & total density. Trabecular bone volume was diminished in CF mice. Female CF mice revealed decreased trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 45 publications
(64 reference statements)
3
29
0
3
Order By: Relevance
“…For example, osteoporosis is a common complication in CF patients and osteopenia has been observed in CF mouse models (14,19,37). Whether this decrease in bone mineral density is directly due to absence of CFTR from cell types found in bone (47) or a secondary effect due to endocrine dysfunction or even perturbations in calcium homeostasis due to absence of CFTR from the gut, kidney (1), or other tissue is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, osteoporosis is a common complication in CF patients and osteopenia has been observed in CF mouse models (14,19,37). Whether this decrease in bone mineral density is directly due to absence of CFTR from cell types found in bone (47) or a secondary effect due to endocrine dysfunction or even perturbations in calcium homeostasis due to absence of CFTR from the gut, kidney (1), or other tissue is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, bone density, which shows little relationship to cord blood IGF1 (20), did not differ by genotype. Decreased bone mineral density has been reported in CF mice, but these studies have tended to focus on older mice (21)(22)(23)(24). Whether bone mineral density will decrease with time in CF pigs and whether IGF1 will contribute to this process remain to be determined.…”
Section: Cf Pigs Showmentioning
confidence: 99%
“…These data raised the hypothesis that the Cftr gene may play a role in cell differentiation and bone matrix maturation ( Table 1). The use of mouse models with a Cftr invalidation or with the F508 mutation in Cftr eliminates other clinical parameters, namely lung disease and chronic malnutrition that are absent in these models [61,62]. Genetic studies in Cftr−/− mice have shown that Cftr invalidation causes low bone mass and altered microarchitecture, a phenotype associated with decreased bone formation and increased bone resorption [61,63,64].…”
Section: Cftr Dysfunction In Bone Cellsmentioning
confidence: 99%
“…The use of mouse models with a Cftr invalidation or with the F508 mutation in Cftr eliminates other clinical parameters, namely lung disease and chronic malnutrition that are absent in these models [61,62]. Genetic studies in Cftr−/− mice have shown that Cftr invalidation causes low bone mass and altered microarchitecture, a phenotype associated with decreased bone formation and increased bone resorption [61,63,64]. More recently, Stalvey and colleagues demonstrated altered osteoblast differentiation with reduced OPG production in cultured calvaria cells from Cftr−/− mice [39].…”
Section: Cftr Dysfunction In Bone Cellsmentioning
confidence: 99%
See 1 more Smart Citation